Peranan Kepemimpinan Kepala Desa terhadap Kinerja Perangkat Desa di Desa Cinunuk Kecamatan Cileunyi Kabupaten Bandung - Nunung, Dede; Fauziya, Fizi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Every organization has a leader who is responsible for all aspects of the organization. The organization will run smoothly if the role owned by the leader in the form of leadership in an organization is carried out with the best possible goals. However, if the government is not run by the existing good norms, it is found that various problems will damage the performance of its subordinates. This research is a quantitative research method with a survey method to obtain data. Research activities by collecting data by collecting using questionnaires or questionnaires in written form which are answered or submitted by respondents. The results found in this research data are based on the responses of 19 respondents to angles and questionnaires. The data found by researchers in the next step will be tested using Validity and further testing with Reliability with an analytical tool in the form of SPSS. In addition, the data used by researchers with model analysis is in the form of simple regression, the coefficient of determination assessment or what can be called R2 and analysis tests using the t-test. Based on the findings of the influence found in the variable in the form of leadership used by the Head of Cinunuk Village on the performance of his apparatus, it is proven by a significant a = 0.001 with a t-count value of 4.174 and a significance of being above 0.05 which is found with 0.001 which means that the hypothesis Ho is rejected and Haha accepted. As a result, the role found in leadership can have a direct positive impact on the variables used by researchers in the form of the performance of village officials in the Cinunuk area, Cileunyi District, Bandung Regency. Keywords: Leadership, Performance.